The Association Between Saturated Fatty Acids (SFAs) Level in Dietary and Blood During Pregnancy and SFAs Level in Breast Milk of Postpartum Mothers - Salehah Nuladani Halimah; Katrin Roosita; Dodik Briawan; Mira Dewi , (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Saturated fatty acids (SFAs) in breast milk are essential for infant’s metabolism as a major metabolic fuel and a low level of SFAs in breast milk might be detrimental for infants’ growth. SFAs in breast milk is determined by maternal SFAs intake and blood levels. Several studies on maternal SFAs have been conducted on breastfeeding mothers but rarely conducted in pregnant women, meanwhile there is an increased SFAs in intake and blood levels in pregnant women on their third trimester due to fat mobilization. This study aims to analyze the relationship between SFAs level in dietary and blood during pregnancy to their levels in breast milk. This research was a longitudinal study and some research data were derived from the BSEA and IPB main research in May-December 2018 at two Bogor City Health Centers, Indonesia. Ninety-eight pregnant women were selected through consecutive sampling method. The data analysis was using Spearman test and Multiple logistic regression. There is no significant relation between SFAs level in dietary with SFAs level in blood. However, dietary intake of lauric acid and total SFAs were significantly associated with lauric acid and total SFAs in breast milk (p<0.05), but not significantly correlated with other types of SFAs (p>0.05). The level of capric, myristate, palmitic, behenic, and lignoceric acids in blood is associated with corresponding SFAs (p<0.05). As a conclusion, SFAs intake in third semester of pregnancy is allowed since increased SFAs in breast milk is important for infants’ early growth.